Konflik Kepentingan Antara Pimpinan Daerah dan DPRD Dalam Penyusunan Anggaran Pendapatan Belanja Daerah - Anastacia Patricia Novlina Nurak; Sri Budi Eko Wardani (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2021)
This research aims to explain about conflict between Sikka’s Local Leader and the Local Legislative Assembly (DPRD) in preparation of Local Government Budget (APBD) for term 2019 year. Sikka regencies is one of district that led by candidate from independent line. Fransiskus Roberto Diogo, (Roby Idong) and Romanus Woga won the District Election Head at 2018 without any party nor coalition. Problem arise when Local Leaders and members of Local Legislative Assembly did not reach mutual agreement about house and communication allowance budget. This research uses qualitative methods with primary data sourced from in-depth interviews with all parties in the conflict. This research used Maswadi Rauf's conflict theory, which is classified based on the results of research by Mark and Synder. In addition, it is known that there are conflicting interests between Local Leader and Local Legislative Assembly about budgeting. Meanwhile, Local Leader in Sikka aim to control Local Legislative Assembly with negative issue about marking up budget of house and transportation allowances, but thus assembly obtain to increase the budgeting for their right.